Reducing Oral Health Disparities: What Can We Learn from Social; Environmental and Cultural Factors? - Sarah R. Baker (Frontiers Research Topics, 2017)
Oral health disparities are profound worldwide, and they affect the quality of life of individuals of all age groups. Disparities in oral health are seen in racial and ethnic minorities, at different socioeconomic levels and due to differences in environment and cultural factors. Several determinants of oral health have been identified at the population, community, family and individual levels. These determinants represent a complex interplay of the social, biological, cultural and economic factors that in turn affect the oral health behaviors, environmental exposures, health care utilization. To date, biological factors related to oral diseases have received much attention in oral health research; whilst social and cultural determinants have just started to receive recognition for their role in oral disease development and progression. This research highlights that interventions designed to reduce disparities should adopt a multi-level approach in order to identify the modifiable mechanisms and target all determinants of oral health disparities. In this Research Topic, we will focus on the role of social, environmental and cultural factors in the development and progression of oral diseases, their role in oral health disparities and interventions focusing on these factors to improve oral health and reduce disparities.